P344 Effectiveness and safety of switching patients with inflammatory bowel disease from originator infliximab to CT-P13: systematic review and meta-analysis. (27th May 2021) - Hanzel, J; Strik, A; Gecse, K; D'Haens, G; Dreesen, E
Abstract: Background: Switching from originator infliximab (IFX) to the CT-P13 biosimilar is a widespread practice, although some concerns persist, particularly about long-term outcomes. We performed a systematic review and meta-analysis to assess the effectiveness and safety of switching from originator IFX to CT-P13 in patients with inflammatory bowel disease (IBD). Methods: We systematically searched electronic databases for randomised controlled trials and prospective observational studies of adult patients with IBD who had switched from originator IFX to CT-P13 and were followed up for at least 12 months. The main outcomes were the pooled rate of clinical remission (as defined by the included studies) and adverse events at 12 months. Secondary outcomes included the rate of treatment discontinuation and de novo immunogenicity. A DerSimonian-Laird random-effects meta-analysis of proportions with double arcsine transformation was performed. Variables judged to be clinically important were studied in an exploratory random-effects meta-regression analysis. Results: Eleven studies with 1204 patients (71% with Crohn's disease [CD]) switching from originator IFX to CT-P13 were identified. Pooled rates of clinical remission at 12 months were 83.6% in ulcerative colitis (UC), 75.9% in CD, and 79.6% in mixed cohorts (Figure 1). Clinical remission at 12 months was negatively associated with combined immunosuppression at switch (7% decrease in remission at 12 months per 10% increase in patients receiving combination therapy) and positively associated with remission at switch (6% increase in remission at 12 months per 10% increase in remission at switch). The pooled rate of adverse events at 12 months was 21.0% (95% confidence interval [CI] 10.4–34.1%). Pooled rates of treatment discontinuation at 12 months were 24.4% (95% CI 12.0–39.4%) in UC, 18.6% (95% CI 8.8–30.9%) in CD, and 13.1% (95% CI 0.7–35.6%) in mixed cohorts. De novo immunogenicity was rare (3.3%, 95% CI 1.5–5.6%). All estimates had at least moderate heterogeneity. Figure 1: Meta-analysis of clinical remission rates at 12 months after switching from originator infliximab to CT-P13 in ulcerative colitis and Crohn's disease. Conclusion: Switching from originator IFX to CT-P13 appears to be effective and safe, although these findings should be interpreted in the context of the limitations of the primary publications which lacked control arms. Combined immunosuppression at switch, potentially as a marker of disease severity, was negatively associated with clinical remission at 12 months after the switch.